Microstructure investigation of semi-polar (11-22) GaN overgrown on differently designed micro-rod array templates - Yaonan Hou (Applied Physics Letters, 2016)
In order to realize semi-polar (11-22) GaN based laser diodes grown on sapphire, it is necessary to further improve the crystal quality of the (11-22) GaN obtained by using our overgrowth approach developed on regularly arrayed micro-rod templates [T. Wang, Semicond. Sci. Technol. 31, 093003 (2016)]. This can be achieved by carefully designing micro-rod templates. Based on transmission electron microscopy and photoluminescence measurements, it has been found that the micro-rod diameter plays a vital role in effectively reducing both the dislocation density and the basal staking fault (BSF) density of the overgrown (11-22) GaN, but in different manners. The BSF density reduces monotonically with increasing the micro-rod diameter from 2 to 5 μm, and then starts to be saturated when the micro-rod diameter further increases. In contrast, the dislocation density reduces significantly when the micro-rod diameter increases from 2 to 4 μm, and then starts to increase when the diameter further increases to 5 μm. Furthermore, employing shorter micro-rods is useful for removing additional BSFs, leading to further improvement in crystal quality. The results presented provide a very promising approach to eventually achieving (11-22) semi-polar III-nitride laser diodes.